Organizational Imaginary and Tacit Dimension of Knowledge: a Case Study in a Telecommunications Company - Marcia Caldas Pitrowsky; Isabel de Sá Affonso da Costa; Denise Medeiros Ribeiro Salles (BBR: Brazilian Business Review, 2014)
This study investigated the relationship between organizational imaginary and tacit dimension of knowledge creation, according to Nonaka and Takeuchi (1997) model, in a telecommunications company. This choice is justified because such segment is highly competitive and knowledge-intensive. Qualitative approach and case study strategy were used, based on documentary analysis, semi-structured interviews and application of projective techniques in workshops. The results showed that the lack of organizational intention concerning the collective commitment to knowledge creation, in a manner clearly articulated by senior management, fails to leverage the existing fertile grounds for innovation, having in view the spontaneous commitment shown by its employees with the image of the company, which is great in their point of view.